Heat-conducting gel with high elongation at break and preparation method thereof

By using new powder treatment agents and special silicon oil in thermal gel to improve the elongation and deformation capacity of thermal gels, the reliability problem of vibration and large displacement of new energy vehicles has been solved, and efficient Heating performance.

CN119350852APending Publication Date: 2025-01-24SHANGHAI HUITIAN NEW CHEMICAL MATERIALS CO LTD

Patent Information

Application Number
CN202411543167.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When existing thermal conductivity gels face dynamic application scenarios of vibration and large displacement in new energy vehicles, they are difficult to meet high elongation of break and good thermal conductivity, and they have reliability problems.

Method used

A new powder treatment agent is used to modify the powder to increase the surface coverage of the powder, and special silicone oil with a special structure and appropriate molecular weight is selected to improve the displacement capacity between organic silicone polymer segments, and the ratio of silicone oil and additives is optimized to prepare Produces 100-1000% high elongation at break thermal conductive gel.

Benefits of technology

The high reliability of the thermal gel under long -term vibration and dynamic operation has excellent deformation ability and good thermal conductivity, and it is suitable for cooling application scenarios in the field of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides heat-conducting gel with high elongation at break and a preparation method of the heat-conducting gel. The heat-conducting gel comprises a first component and a second component, the first component is prepared from the following components in parts by mass: 100 to 500 parts of heat-conducting filler, 10 to 100 parts of vinyl-terminated polydimethylsiloxane, 0.4 to 4 parts of powder treating agent, 1 to 10 parts of special silicone oil, 0.1 to 1 part of platinum catalyst, 0 to 1 part of antioxidant and 0 to 1 part of toner or color paste; the second component is prepared from the following components in parts by mass: 100 to 500 parts of heat-conducting filler, 10 to 100 parts of vinyl-terminated polydimethylsiloxane, 1 to 10 parts of terminated hydrogen-containing silicone oil, 1 to 10 parts of side hydrogen-containing silicone oil, 0.4 to 4 parts of powder treating agent, 1 to 10 parts of special silicone oil, 0.1 to 1 part of inhibitor, 0 to 1 part of antioxidant and 0 to 1 part of toner or color paste. The heat-conducting gel is used for solving the reliability problem of the heat-conducting gel under long-term vibration and dynamic operation; special silicone oil is introduced, so that the surface coverage rate of the powder is increased, and the displacement capacity between organosilicone polymer chain segments is improved; the material has high elongation at break and good deformability so as to adapt to heat dissipation application scenes in the field of new energy automobiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive interface materials, and in particular to a thermal conductive gel with high elongation at break and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles and the continuous upgrading of intelligent driving systems, there are more and more power semiconductor components on passenger cars, such as IGBT modules, MOSFETs, DC / DC converters and various AI chips, and the heat generated is also increasing. In the face of the continuous upgrading of new energy vehicles, heat dissipation has gradually become a new challenge for new energy vehicles in terms of performance improvement and safety management.

[0003] Different from the static application scenarios of general thermal conductive gels, thermal conductive interface materials used in the new energy field face dynamic application scenarios such as vibration and large displacement during operation. Therefore, it is extremely necessary for thermal conductive gels to have a sufficiently high elongation at break to ensure large deformation capability and long-term reciprocating displacement capability to help cope with this scenario.

[0004] Thermally conductive gel is usually based on reactive silicone oil, and then filled with a large amount of fillers with high thermal conductivity. The thermal conductivity of common thermal conductive fillers such as alumina is about 30 W / m·K, aluminum nitride is 80~320 W / m·K, and the thermal conductivity of silicone oil is only 0.14~0.16W / m·K. Based on the thermal path theory, the thermal conductivity will only be improved at a higher filling rate and when a thermal conductive path is formed inside. For elastomeric materials, too high a filling rate will lead to an increase in modulus and a decrease in elongation at break; at the same time, the larger the size of the thermal conductive filler, the better the thermal conductivity improvement effect, and the smaller the elongation at break. Therefore, thermal conductivity and elongation at break are opposite to each other. At present, the elongation at break of common thermal conductive gels on the market is generally between 30~200%.

[0005] After searching, it was found that in the field of thermal conductive gel in China, only a few patents involve elongation at break, such as: CN116949405A, CN117801283A, CN115926474A, CN116265530A and CN111154269A, etc., which disclose the preparation of thermal conductive gel with high elongation at break. However, the average elongation at break of these embodiments is between 100% and 200%, and only the embodiment in CN116949405A has an elongation at break of 400% at a relatively low thermal conductivity (1.5 W / m·K). In this case, it is difficult to cope with the large displacement caused by vibration, and it is difficult to sacrifice more thermal conductivity in exchange for elongation at break, so it is difficult to meet the growing thermal management needs in the field of new energy vehicles.

[0006] Based on this, the present invention proposes a novel thermal conductive gel with high elongation at break and a preparation method thereof. Summary of the invention

[0007] Based on the above description, the present invention provides a thermally conductive gel with high elongation at break and a preparation method thereof, so as to solve the reliability problem of the thermally conductive gel in the prior art under long-term vibration and dynamic operation.

[0008] The technical solution of the present invention to solve the above technical problems is as follows: In a first aspect, the present invention provides a thermally conductive gel with high elongation at break, comprising a first component and a second component; The first component includes the following raw materials by weight: 100-500 parts of thermal conductive filler, 10-100 parts of vinyl-terminated polydimethylsiloxane, 0.4-4 parts of powder treatment agent, 1-10 parts of special silicone oil, 0.1-1 parts of platinum catalyst, 0-1 parts of antioxidant, and 0-1 parts of color powder or color paste; The second component includes the following raw materials by mass: 100-500 parts of thermal conductive filler, 10-100 parts of terminal vinyl polydimethylsiloxane, 1-10 parts of terminal hydrogen-containing silicone oil, 1-10 parts of side hydrogen-containing silicone oil, 0.4-4 parts of powder treatment agent, 1-10 parts of special silicone oil, 0.1-1 parts of inhibitor, 0-1 parts of antioxidant, and 0-1 parts of color powder or color paste.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Further, the thermally conductive filler includes at least one of aluminum, aluminum oxide, aluminum nitride, boron nitride, zinc oxide, and aluminum hydroxide; Wherein, the aluminum oxide is high α-phase spherical aluminum oxide, and the aluminum nitride is spherical aluminum nitride.

[0011] Furthermore, the vinyl-terminated polydimethylsiloxane includes at least one of a vinyl-terminated polydimethylsiloxane having a viscosity of 450-550 mPa·s and a vinyl content of 1.05-1.1 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 900-1100 mPa·s and a vinyl content of 0.8-1.0 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 2700-3300 mPa·s and a vinyl content of 0.5-0.55 wt %, and a vinyl-terminated polydimethylsiloxane having a viscosity of 4500-5500 mPa·s and a vinyl content of 0.38-0.42 wt %.

[0012] Furthermore, the platinum catalyst is at least one of a Custer catalyst, an Ashby catalyst and a single-component high-temperature platinum catalyst; wherein the platinum content is between 3000 and 10000 ppm.

[0013] Furthermore, the molecular structure of the special silicone oil is Y-(Si-O) x -Si(OR) y , where (OR) y represents an alkoxy structure; Y is a functional group; X is the number of main chain structural units, which is between 10 and 100.

[0014] Furthermore, the toner includes at least one of cobalt blue, iron red, carbon black, and cadmium yellow, or a color paste formed by dispersing the toner in silicone oil.

[0015] Further, the hydrogen content of the hydrogen-terminated silicone oil is 0.15-1.0 mmoles / g, and the viscosity ranges from 10 to 200 cSt at 25°C; The hydrogen content of the side hydrogen-containing silicone oil is 0.9-12 mmoles / g, and the viscosity range at 25° C. is 10-200 cSt.

[0016] Further, the powder treatment agent includes at least one of methyltrimethoxysilane, dodecyltrimethoxysilane, dodecasiloxytrimethoxysilane, dodecasiloxytrimethylethylsilane, hexadecyloxytrimethoxysilane, hexadecyloxytriethoxysilane, hexadecyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0017] Further, the inhibitor is at least one of a polyvinyl polymer, ethynyl cyclohexanol and trimethyldodecyl acetylenic alcohol; The antioxidant is any one of cerium oxide, hydroquinone, 2-tert-butylphenol, 3,5-di-tert-butyl-4-hydroxyphenylpropionate and antioxidant 2246.

[0018] In a second aspect, the present invention provides a method for preparing the thermally conductive gel with high elongation at break as described in the first aspect, comprising the following steps: Adding vinyl-terminated polydimethylsiloxane, powder treatment agent, special silicone oil, thermal conductive filler, platinum catalyst and antioxidant into a planetary mixer according to the proportion, mixing and performing vacuum degassing treatment to obtain a first component; Vinyl-terminated polydimethylsiloxane, powder treatment agent, special silicone oil, hydrogen-terminated polydimethylsiloxane, methyl-terminated methylhydrogensiloxane, thermal conductive filler, inhibitor, antioxidant and color paste are added into a planetary mixer according to the proportion, mixed and vacuum degassing treatment is carried out to obtain the second component.

[0019] Compared with the prior art, the technical solution of this application has the following beneficial technical effects: The high elongation at break thermal conductive gel and the preparation method thereof provided by the present invention are mainly used to solve the reliability problem of the thermal conductive gel under long-term vibration and dynamic operation; the powder is modified by adopting a new powder treatment agent to improve the surface coverage of the powder; at the same time, special silicone oil with a special structure and appropriate molecular weight is selected to improve the displacement capacity between silicone polymer chain segments; and the ratio of silicone oil to additives is optimized to prepare a type of thermal conductive gel with a high elongation at break of 100-1000% and good deformation ability to adapt to the heat dissipation application scenarios in the field of new energy vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a stress-strain curve diagram of the thermally conductive gel with high elongation at break provided in Examples 1 and 2 of the present invention.

[0021] Figure 2 This is a tensile test of the high elongation at break thermally conductive gel provided in Examples 1 and 2 of the present invention on a tensile testing machine. The left and right figures are photos before and after stretching, respectively.

[0022] Figure 3 The stress-strain curves of the thermally conductive gels with high elongation at break provided by Examples 3 and 4 of the present invention and the thermally conductive gels provided by Comparative Examples 1 and 2 are shown.

[0023] Figure 4 This is a tensile test of the high elongation at break thermally conductive gel provided in Examples 3 and 4 of the present invention on a tensile testing machine. The left and right figures are photos before and after stretching, respectively. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The following is combined with Figures 1 to 4 The embodiments of the present invention are further described in detail with examples. The following examples are used to illustrate the present invention but cannot be used to limit the scope of the present invention.

[0026] The invention provides a thermal conductive gel with high elongation at break, comprising a first component and a second component.

[0027] The first component includes the following raw materials by mass: 100-500 parts of thermal conductive filler, 10-100 parts of vinyl-terminated polydimethylsiloxane, 0.4-4 parts of powder treatment agent, 1-10 parts of special silicone oil, 0.1-1 parts of platinum catalyst, 0-1 parts of antioxidant, and 0-1 parts of color powder or color paste.

[0028] The second component includes the following raw materials by mass: 100-500 parts of thermal conductive filler, 10-100 parts of terminal vinyl polydimethylsiloxane, 1-10 parts of terminal hydrogen-containing silicone oil, 1-10 parts of side hydrogen-containing silicone oil, 0.4-4 parts of powder treatment agent, 1-10 parts of special silicone oil, 0.1-1 parts of inhibitor, 0-1 parts of antioxidant, and 0-1 parts of color powder or color paste.

[0029] Wherein, the thermal conductive filler includes at least one of aluminum, aluminum oxide, aluminum nitride, boron nitride, zinc oxide, and aluminum hydroxide; Wherein, the aluminum oxide is high α-phase spherical aluminum oxide, and the aluminum nitride is spherical aluminum nitride.

[0030] The vinyl-terminated polydimethylsiloxane includes at least one of a vinyl-terminated polydimethylsiloxane having a viscosity of 450-550 mPa·s and a vinyl content of 1.05-1.1 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 900-1100 mPa·s and a vinyl content of 0.8-1.0 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 2700-3300 mPa·s and a vinyl content of 0.5-0.55 wt %, and a vinyl-terminated polydimethylsiloxane having a viscosity of 4500-5500 mPa·s and a vinyl content of 0.38-0.42 wt %.

[0031] The platinum catalyst is at least one of a Custer catalyst, an Ashby catalyst and a single-component high-temperature platinum catalyst; wherein the platinum content is between 3000 and 10000 ppm.

[0032] The molecular structure of special silicone oil is Y-(Si-O) x -Si(OR) y , where (OR) y represents an alkoxy structure; Y is a functional group, which can be a methyl group, a vinyl group, an amino group, a secondary amine group, an epoxy group, a hydroxyl group or a hydrogen group; X is the number of main chain structural units, which is between 10 and 100.

[0033] The color powder includes at least one of cobalt blue, iron red, carbon black, and cadmium yellow, or a color paste formed by dispersing the color powder in silicone oil.

[0034] The hydrogen content of the terminal hydrogenated silicone oil is 0.15-1.0 mmoles / g, and the viscosity range is 10-200 cSt at 25°C.

[0035] The hydrogen content of the side hydrogen silicone oil is 0.9-12 mmoles / g, and the viscosity range is 10-200 cSt at 25°C.

[0036] The powder treatment agent includes at least one of methyltrimethoxysilane, dodecyltrimethoxysilane, dodecasiloxytrimethoxysilane, dodecasiloxytrimethylethylsilane, hexadecyloxytrimethoxysilane, hexadecyloxytriethoxysilane, hexadecyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0037] The inhibitor is at least one of a polyvinyl polymer, ethynyl cyclohexanol, and trimethyldodecyl acetyl alcohol; The antioxidant is any one of cerium oxide, hydroquinone, 2-tert-butylphenol, 3,5-di-tert-butyl-4-hydroxyphenylpropionate and antioxidant 2246.

[0038] Example 1 The high elongation at break thermal conductive gel and the preparation method thereof provided in this embodiment include the following steps: Step S1: 100 parts of thermal conductive filler (60 parts of spherical alumina with a median particle size of 10 μm, 40 parts of alumina with a median particle size of 1 μm), 1 part of powder treatment agent, 6 parts of special silicone oil, and 5 parts of double-ended vinyl silicone oil of 5000 mPa·s are added to a planetary power mixer for mixing; the temperature is raised to 180° C., and the mixture is stirred at a rate of 50 rpm and dispersed at 500 rpm for 1 hour at a pressure of -0.1 MPa; the mixture is cooled to below 50° C., 0.2 parts of catalyst and 0.1 parts of color paste are added, and the mixture is dispersed for 10 minutes before discharging and vacuum degassing is performed to obtain the first component.

[0039] Step S2: 100 parts of thermal conductive filler (60 parts of spherical alumina with a median particle size of 10 μm, 40 parts of alumina with a median particle size of 1 μm), 1 part of powder treatment agent, 6 parts of special silicone oil, and 4.45 parts of 5000 mPa·s double-ended vinyl silicone oil are added to a planetary power mixer for mixing; the temperature is raised to 180° C., and the mixture is stirred at 50 rpm and dispersed at 500 rpm for 1 hour at a pressure of -0.1 MPa; the mixture is cooled to below 50° C.; 0.65 parts of hydrogenated silicone oil, 0.1 parts of inhibitor, and 0.1 parts of color paste are added, and the mixture is dispersed for 10 minutes before discharging and vacuum degassing to obtain the second component.

[0040] Example 2 The high elongation at break thermal conductive gel and preparation method thereof provided in this embodiment are different from those in Embodiment 1 in that: Step S1: The process steps are the same as step S1 in Example 1, except that the special silicone oil is 4 parts and the double-terminated vinyl silicone oil of 500 mPa·s is 7 parts.

[0041] Step S2: The process steps are the same as step S2 in Example 1, except that 4 parts of special silicone oil, 6.45 parts of 500 mPa·s double-terminated vinyl silicone oil, and 1 part of hydrogen-containing silicone oil are used.

[0042] Example 3 The high elongation at break thermal conductive gel and preparation method thereof provided in this embodiment are different from those in Embodiment 1 in that: Step S1: The process steps are the same as step S1 in Example 1, except that 100 parts of thermal conductive filler (60 parts of spherical alumina with a median particle size of 20 μm, 40 parts of alumina with a median particle size of 1 μm), 4 parts of silicone oil, and 3 parts of 500 mPa·s double-ended vinyl silicone oil are used.

[0043] Step S2: The process steps are the same as step S2 in Example 1, except that 100 parts of thermal conductive filler (60 parts of spherical alumina with a median particle size of 20 μm, 40 parts of alumina with a median particle size of 1 μm), 4 parts of special silicone oil, 3.45 parts of 500 mPa·s double-ended vinyl silicone oil, and 0.65 parts of hydrogenated silicone oil are used.

[0044] Example 4 The high elongation at break thermal conductive gel and preparation method thereof provided in this embodiment are different from those in Embodiment 1 in that: Step S1: The process steps are the same as step S1 in Example 1, except that 100 parts of thermal conductive filler (60 parts of aluminum powder with a median particle size of 20 μm, 25 parts of aluminum powder with a median particle size of 1 μm, 15 parts of zinc oxide with a median particle size of 0.3 μm), 4 parts of special silicone oil, and 4 parts of 500 mPa·s double-terminal vinyl silicone oil are used.

[0045] Step S2: The process steps are the same as step S2 in Example 1, except that 100 parts of thermal conductive filler (60 parts of aluminum powder with a median particle size of 20 μm, 25 parts of aluminum powder with a median particle size of 1 μm, 15 parts of zinc oxide with a median particle size of 0.3 μm), 4 parts of special silicone oil, 3.45 parts of 100 mPa·s double-terminal vinyl silicone oil, and 0.6 parts of hydrogen-containing silicone oil are used.

[0046] Comparative Example 1 This comparative example provides a conventional two-component thermally conductive gel, and its preparation method comprises the following steps: Step S1: The process steps are the same as step S1 in Example 1, except that 100 parts of thermal conductive filler (60 parts of spherical alumina with a median particle size of 45 μm, 20 parts of alumina with a median particle size of 5 μm, and 20 parts of alumina with a median particle size of 1 μm), 0.5 parts of powder treatment agent, 3 parts of 300 mPa·s methyl silicone oil, and 3 parts of 500 mPa·s double-ended vinyl silicone oil.

[0047] Step S2: The process steps are the same as step S2 in Example 1, except that there are 100 parts of thermal conductive filler (60 parts of spherical alumina with a median particle size of 20 μm, 20 parts of alumina with a median particle size of 5 μm, and 20 parts of alumina with a median particle size of 1 μm), 0.5 parts of powder treatment agent, 3 parts of 300 mPa·s methyl silicone oil, 2.5 parts of 500 mPa·s double-ended vinyl silicone oil, and 0.45 parts of hydrogenated silicone oil.

[0048] Comparative Example 2 This comparative example provides a conventional two-component thermally conductive gel, and its preparation method comprises the following steps: Step S1: The process steps are the same as step S1 in Example 1, except that 100 parts of thermal conductive filler (60 parts of spherical aluminum nitride with a median particle size of 45 μm, 20 parts of aluminum oxide with a median particle size of 5 μm, and 20 parts of aluminum oxide with a median particle size of 1 μm), 0.5 parts of powder treatment agent, 2 parts of 300 mPa·s methyl silicone oil, and 2 parts of 500 mPa·s double-ended vinyl silicone oil.

[0049] Step S2: The process steps are the same as step S2 in Example 1, except that there are 100 parts of thermal conductive filler (60 parts of spherical aluminum nitride with a median particle size of 45 μm, 20 parts of aluminum oxide with a median particle size of 5 μm, and 20 parts of aluminum oxide with a median particle size of 1 μm), 0.5 parts of powder treatment agent, 2 parts of 300 mPa·s methyl silicone oil, 1.5 parts of 500 mPa·s double-ended vinyl silicone oil, and 0.45 parts of hydrogenated silicone oil.

[0050] Comparative Example 3 This comparative example provides a commercially available 2.5W thermal conductive gel, specifically a 2.5W thermal conductive gel of model TC-4025 from the DOWSIL™ series of Dow Chemical Company.

[0051] Comparative Example 4 The comparative example provides a commercially available 2.5W thermal conductive gel, specifically a 2.5W thermal conductive gel of model TIA225GF from the SILCOOL™ series of MOMENTIVE.

[0052] Comparative Example 5 This comparative example provides a commercially available 4W thermal conductive gel, specifically a 4W thermal conductive gel of model TC-4040 from the DOWSIL™ series of Dow Chemical Company.

[0053] The thermally conductive gels obtained in the above examples and comparative examples were tested for performance, and the corresponding performance comparisons are shown in Table 1: Table 1 Performance comparison of Examples 1 to 4 and Comparative Examples 1 to 5

[0054] According to the thermal permeation theory, at low filling, the thermal conductive filler will be evenly dispersed in the polymer to form a "sea-island" structure instead of a continuous structure. At this time, the thermal conductivity will slowly increase with the filling rate. When the volume filling rate reaches the permeation threshold, the thermal conductive filler will form a "sea-sea" structure, which will significantly increase the thermal conductivity.

[0055] Figure 2 The figure shows the tensile test of the high elongation at break thermal conductive gel provided in Examples 1 and 2 on a tensile machine, the left and right figures are photos before and after stretching respectively; Figure 1 It can be seen that the high elongation at break thermally conductive gels provided in Examples 1 and 2 have very high elongation at break, which is 4 to 10 times higher than the elongation at break of some products on the market, and have excellent deformation capacity. The alkoxy structure of the special silicone oil makes it more polar than conventional silicone oil, which can well increase the compatibility with the powder and improve the elongation at break; at the same time, the appropriate molecular weight is conducive to keeping the gel from stratification under large spacing changes, avoiding defects that lead to premature fracture; and the modulus of the thermally conductive gel is regulated by a series of additives and the amount of hydrogen-containing silicone oil, further maximizing the deformation capacity.

[0056] further, Figure 4 The figure shows the tensile test of the high elongation at break thermal conductive gel provided in Examples 3 and 4 on a tensile machine, the left and right figures are photos before and after stretching respectively; Figure 3 As can be seen from Table 1, by comparing Examples 1 to 4, it can be found that when the volume filling rate reaches a certain level, increasing the thermal conductivity will lead to a decrease in the elongation at break, especially in Example 4, where the elongation at break of the high elongation thermal conductive gel provided in Example 3 is 514.9% and the thermal conductivity is 3.9 W / m·K; the elongation at break of the high elongation thermal conductive gel provided in Example 4 is 97.5% and the thermal conductivity is 6.0 W / m·K. From a microscopic point of view, the "sea-sea" structure under high volume filling has a great damage to the continuous phase of the polymer, and then more defects will be generated in the tensile deformation, resulting in fracture.

[0057] It can be found from the examples and comparative examples that, under the same thermal conductivity, i.e., similar volume filling rate, the special silicone oil can effectively increase the elongation at break, improve the ductility, and give the thermally conductive gel excellent elasticity and deformation ability.

[0058] The high elongation at break thermally conductive gels prepared in Examples 1 to 4 all have room temperature curing, high temperature accelerated curing, high flow rate and excellent dispensing process performance. After curing, the gel has low modulus, high elongation at break, high deformation capacity, can withstand long-term vibration to ensure adhesion without debonding, meet the performance and durability requirements of high thermal conductive gels in mobile energy storage and electronic fields such as new energy, power batteries, automotive electronics and consumer electronics, improve the reliability of mobile applications, and have broad prospects for use.

[0059] In summary, compared with the prior art, this embodiment can achieve the following technical effects: The high elongation at break thermal conductive gel and the corresponding preparation method provided in the embodiments of the present invention are mainly used to solve the reliability problem of the thermal conductive gel under long-term vibration and dynamic operation; the powder is modified by adopting a new powder treatment agent to improve the surface coverage of the powder; at the same time, special silicone oil with special structure and appropriate molecular weight is selected to improve the displacement ability between silicone polymer chain segments; and the ratio of silicone oil to additives is optimized to prepare a type of thermal conductive gel with a high elongation at break of 100-1000% and good deformation ability to adapt to the heat dissipation application scenarios in the field of new energy vehicles.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A thermally conductive gel with high elongation at break, characterized in that: comprising a first component and a second component; The first component includes the following raw materials by weight: 100-500 parts of thermal conductive filler, 10-100 parts of vinyl-terminated polydimethylsiloxane, 0.4-4 parts of powder treatment agent, 1-10 parts of special silicone oil, 0.1-1 parts of platinum catalyst, 0-1 parts of antioxidant, and 0-1 parts of color powder or color paste; The second component includes the following raw materials by mass: 100-500 parts of thermal conductive filler, 10-100 parts of terminal vinyl polydimethylsiloxane, 1-10 parts of terminal hydrogen-containing silicone oil, 1-10 parts of side hydrogen-containing silicone oil, 0.4-4 parts of powder treatment agent, 1-10 parts of special silicone oil, 0.1-1 parts of inhibitor, 0-1 parts of antioxidant, and 0-1 parts of color powder or color paste.

2. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The thermally conductive filler includes at least one of aluminum, aluminum oxide, aluminum nitride, boron nitride, zinc oxide, and aluminum hydroxide; Wherein, the aluminum oxide is high α-phase spherical aluminum oxide, and the aluminum nitride is spherical aluminum nitride.

3. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The vinyl-terminated polydimethylsiloxane comprises at least one of a vinyl-terminated polydimethylsiloxane having a viscosity of 450-550 mPa·s and a vinyl content of 1.05-1.1 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 900-1100 mPa·s and a vinyl content of 0.8-1.0 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 2700-3300 mPa·s and a vinyl content of 0.5-0.55 wt %, and a vinyl-terminated polydimethylsiloxane having a viscosity of 4500-5500 mPa·s and a vinyl content of 0.38-0.42 wt %.

4. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The platinum catalyst is at least one of a Custer catalyst, an Ashby catalyst and a single-component high-temperature platinum catalyst; wherein the platinum content is between 3000 and 10000 ppm.

5. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The molecular structure of the special silicone oil is Y-(Si-O) x -Si(OR) y , where (OR) y represents an alkoxy structure; Y is a functional group; X is the number of main chain structural units, which is between 10 and 100.

6. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The toner includes at least one of cobalt blue, iron red, carbon black, and cadmium yellow, or a color paste formed by dispersing the toner in silicone oil.

7. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The hydrogen content of the terminal hydrogenated silicone oil is 0.15-1.0 mmoles / g, and the viscosity range is 10-200 cSt at 25°C; The hydrogen content of the side hydrogen-containing silicone oil is 0.9-12 mmoles / g, and the viscosity range at 25° C. is 10-200 cSt.

8. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The powder treatment agent includes at least one of methyltrimethoxysilane, dodecyltrimethoxysilane, dodecasiloxytrimethoxysilane, dodecasiloxytrimethylethylsilane, hexadecyloxytrimethoxysilane, hexadecyloxytriethoxysilane, hexadecyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

9. The thermally conductive gel with high elongation at break according to claim 1, characterized in that: The inhibitor is at least one of a polyvinyl polymer, ethynyl cyclohexanol and trimethyl dodecyl alkynol; The antioxidant is any one of cerium oxide, hydroquinone, 2-tert-butylphenol, 3,5-di-tert-butyl-4-hydroxyphenylpropionate and antioxidant 2246.

10. A method for preparing a thermally conductive gel with high elongation at break according to any one of claims 1 to 9, characterized in that: The steps include: Adding vinyl-terminated polydimethylsiloxane, powder treatment agent, special silicone oil, thermal conductive filler, platinum catalyst and antioxidant into a planetary mixer according to the proportion, mixing and performing vacuum degassing treatment to obtain a first component; Vinyl-terminated polydimethylsiloxane, powder treatment agent, special silicone oil, hydrogen-terminated polydimethylsiloxane, methyl-terminated methylhydrogensiloxane, thermal conductive filler, inhibitor, antioxidant and color paste are added into a planetary mixer according to the proportion, mixed and vacuum degassing treatment is carried out to obtain the second component.

Citation Information

Patent Citations

  • Low-modulus heat-conducting organopolysiloxane composition as well as preparation method and application thereof

    CN111154269A

  • Low-modulus high-elongation organic silicon heat-conducting gel

    CN115926474A

  • Repairable heat-conducting gel and preparation method thereof

    CN116265530A

  • Application of N-doped Y2O3 film in optical device

    CN116949405A

  • Self-crosslinking vinyl hydrogen-containing silicone oil, heat-conducting gel and preparation method of self-crosslinking vinyl hydrogen-containing silicone oil

    CN117801283A

Cited By

  • Low-hardness high-resilience heat-conducting organic silicon gel and preparation method thereof

    CN120758048A